Crossover of Failure Time Distributions in a Model of Time-Dependent Fracture - Alava, Mikko J. (Frontiers in Physics, 2021)
An important question in the theory of fracture is what kind of life-time distributions may exist for materials under load. Here, this is studied in the context of a one-dimensional fracture model with local load sharing under a constant external load, "creep". Simulations of the system with Weibull distributed initial life-times for the elements show that the limiting distribution follows from extreme statistics and takes the Gumbel form eventually, with longer and longer cross-overs in the system size from a Weibull-like distribution, depending on the initial Weibull-exponent.